Intentional right atrial exit for microcatheter infusion of pericardial carbon dioxide or iodinated contrast to facilitate sub‐xiphoid access. Issue 2 (28th October 2014) - Rogers, Toby; Ratnayaka, Kanishka; Schenke, William H.; Faranesh, Anthony Z.; Mazal, Jonathan R.; O'Neill, William W.; Greenbaum, Adam B.; Lederman, Robert J.
Abstract : Objectives: We test the safety of transatrial pericardial access using small catheters, infusion of carbon dioxide (CO2 ) or iodinated contrast to facilitate sub‐xiphoid access, and catheter withdrawal under full anticoagulation.Background: Sub‐xiphoid pericardial access is required for electrophysiological and structural heart interventions. If present, an effusion protects the heart from needle injury by separating the myocardium from the pericardium. However, if the pericardium is 'dry' then there is a significant risk of right ventricle or coronary artery laceration caused by the heart beating against the needle tip. Intentional right atrial exit is an alternative pericardial access route, through which contrast media could be infused to separate pericardial layers.Methods: Transatrial pericardial access was obtained in a total of 30 Yorkshire swine using 4Fr or 2.8Fr catheters. In 16 animals, transatrial catheters were withdrawn under anticoagulation and MRI was performed to monitor for pericardial hemorrhage. In 14 animals, iodinated contrast or CO2 was infused before sub‐xiphoid access was obtained.Results: Small effusions (mean 18.5 ml) were observed after 4Fr (1.3 mm outer‐diameter) but not after 2.8Fr (0.9 mm outer‐diameter) transatrial catheter withdrawal despite full anticoagulation (mean activated clotting time 383 sec), with no hemodynamic compromise. Pericardial CO2 resorbed spontaneously within 15 min.Conclusions: Intentional transatrial exit into the pericardium using small catheters is safe and permits infusion of CO2 or iodinated contrast to separate pericardial layers and facilitate sub‐xiphoid access. This reduces the risk of right ventricular or coronary artery laceration. 2.8Fr transatrial catheter withdrawal does not cause any pericardial hemorrhage, even under full anticoagulation. © 2014 Wiley Periodicals, Inc.